ELEVATING FIRM VALUE: EXPLORING THE ESG FRAMEWORK'S INFLUENCE ON CORPORATE PERFORMANCE - Wiyarti, Evy Steelyana; Lim, Michelle (JURNAL AKUNTANSI DAN AUDITING, 2024)
The establishment of a company not only focuses on financial aspects, but also focuses on social and environmental aspects. The purpose of this study is to empirically prove that philanthropic activities, environmental performance and environmental costs affect the value of the company. This research was conducted by energy sector companies listed on the Indonesia Stock Exchange in 2011-2020 and used the purposive sampling method  in determining samples. Data processing in this study was carried out using Microsoft Excel and SPSS 25 software. The data analysis technique in this study used multiple linear regression analysis. The results of this study prove that philanthropic activities have a positive and significant impact on the value of the company, while environmental performance has positive results but does not have a significant effect on the value of the enterprise. On the other hand, environmental costs have a negative result and do not have a significant effect on the value of the company. These findings suggest that companies should continue to prioritize philanthropic activities as a component of their CSR strategy, while also considering the environmental costs incurred as a result of their operations.